How to Write a Proof - Lamport, Leslie (American Mathematical Monthly. Also appeared in Global Analysis in Modern Mathematics, Karen Uhlenbeck, editor. Publish or Perish Press, Houston. Also appeared as SRC Research Report 94., 1995)
TLA gave me, for the first time, a formalism in which it was possible to write completely formal proofs without first having to add an additional layer of formal semantics. I began writing proofs the way I and all mathematicians and computer scientists had learned to write them, using a sequence of lemmas whose proofs were a mixture of prose and formulas. I quickly discovered that this approach collapsed under the weight of the complexity of any nontrivial proof. I became lost in a maze of details, and couldn't keep track of what had and had not been proved at any point. Programmers learned long ago that the way to handle complexity is with hierarchical structuring. So, it was quite natural to start structuring the proofs hierarchically, and I soon developed a simple hierarchical proof style. It then occurred to me that this structured proof style should be good for ordinary mathematical proofs, not just for formal verification of systems. Trying it out, I found that it was great. I now never write old-fashioned unstructured proofs for myself, and use them only in some papers for short proof sketches that are not meant to be rigorous. I first presented these ideas in a talk at a celebration of the 60th birthday of Richard Palais, my de jure thesis advisor, collaborator, and friend. I was invited along with all of Palais' former doctoral students, and I was the only non-mathematician who gave a talk. (I believe all the other talks presented that day appear among the articles in the volume edited by Uhlenbeck.) Lots of people jumped on me for trying to take the fun out of mathematics. The strength of their reaction indicates that I hit a nerve. Perhaps they really do think it's fun having to recreate the proofs themselves if they want to know whether a theorem in a published paper is actually correct, and to have to struggle to figure out why a particular step in the proof is supposed to hold. I republished the paper in the AMM Monthly so it would reach a larger audience of mathematicians. Maybe I should republish it again for computer scientists.